2018
DOI: 10.13057/biodiv/d190416
|View full text |Cite
|
Sign up to set email alerts
|

Growth, histochemical and physiological responses of non-edible oil producing plant (Reutealis trisperma) to gold mine tailings

Abstract: Hilmi M, Hamim H, Sulistyaningsih YC, Taufikurahman. 2018. Growth, histochemical and physiological responses of nonedibleoil producing plant (Reutealis trisperma) to gold mine tailings. Biodiversitas 19: 1294-1302. Reutealis trisperma (Blanco) AiryShaw is a non-edible biodiesel producing plant that is able to grow well in various unfavorable environmental conditions. The studyaimed to analyze the growth, physiological, and anatomical responses of R. trisperma to gold mine tailings. Three-month-old of R.trisper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
15
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(22 citation statements)
references
References 50 publications
(53 reference statements)
3
15
0
4
Order By: Relevance
“…Interestingly, in this study, Pb stress had no significant effect on plant height, increased leave number as well as leaves area of Philippine-tung (R. trisperma), suggesting that this species is resistance to Pb. The adaptability of this species to Pb has also been confirmed in other experiments using soil media contained Pb, such as Hilmi et al (2018) who observed various accessions of R. trisperma grown on gold mine tailings contained Pb, and Andriya et al (2019) who compared this species with other non-edible oilproducing plants under gold mine tailings.…”
Section: Discussionsupporting
confidence: 60%
See 3 more Smart Citations
“…Interestingly, in this study, Pb stress had no significant effect on plant height, increased leave number as well as leaves area of Philippine-tung (R. trisperma), suggesting that this species is resistance to Pb. The adaptability of this species to Pb has also been confirmed in other experiments using soil media contained Pb, such as Hilmi et al (2018) who observed various accessions of R. trisperma grown on gold mine tailings contained Pb, and Andriya et al (2019) who compared this species with other non-edible oilproducing plants under gold mine tailings.…”
Section: Discussionsupporting
confidence: 60%
“…Heavy metals especially from non-essential elements such as Pb, Hg, and Cd (Ashraf 2006), may even become more dangerous due to the process of bioaccumulation along the food chains (David et al 2012). Lead (Pb) is an example of heavy metal pollutant produced from industrial wastes such as gold mine tailings (Hilmi et al 2018) which cause a decrease in soil quality and adversely affects plants, animals, humans, and ecosystems. The toxic effects of Pb on plants result in a decrease of plant ability to absorb mineral nutrition, lower water balance, inhibition of root growth, blackening of root system and leaves chlorosis (Nas and Ali 2018).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Generally, mine tailings are considered to have a negative value due to the lower organic matter content, mineral nutrients, cation exchange capacity (CEC), and microorganism activity (Wasis et al 2011), while they have higher heavy metals concentration (Setyaningsih et al 2017). For example, Hidayati et al (2006) and Hilmi et al (2018) found that lead (Pb) contamination in gold mine tailings was 6-20 times greater than land without tailings.…”
Section: Introductionmentioning
confidence: 99%